Individual study of anthropometric variation, energy and macronutrients intakes in Paralympic Track and Field athletes in different phases of the season - Dayane Ferreira Rodrigues; Andressa Silva; Claudia Ridel Juzwiak; Daniel Paduan Joaquim; João Paulo Pereira Rosa; Mário Antônio de Moura Simim; Amaury Wagner Veríssimo; Ciro Winckler; Sergio Tufik; Marco Túlio de Mello (Motriz: Revista de Educacao Fisica, 2018)
Abstract Aims: a) to measure individual variations in body mass (BM), sum of skinfolds (SSF) and energy intake of Paralympic track and field athletes b) to evaluate whether individual consumption of macronutrients meets recommended levels in three distinct periods of training. Methods: Ten Paralympic track and field athletes were evaluated during three periods: 1) end of season, 2) after vacation, and 3) preparation for the Paralympic Games London 2012. Food history and the 24-hour Dietary Recall methods provided information on daily food intake. To assess changes in body composition, we measured skinfolds and BM. Descriptive statistics were utilized to describe individual results. Results: BM varied among athletes and phases, but most (n=8) had higher SSF after vacation. Four athletes reported an increase in energy intake of more than 500 kcal during their vacation period, while eight athletes reported maintaining their intake in the preparatory phase for the competition. Carbohydrate intake was adequate for most athletes in the end of season period and in the preparatory phase for competition, and most athletes had reduced lipid intake after vacation and in the preparatory phase. Conclusion: We observed important variations in BM and SSF, in food intake and macronutrients between the three evaluated periods. The nutritional status of the athletes suggests that inadequacies that might affect the performance of sprinters and middle-distance runners are more likely to occur during the preparatory period before competitions.